Amizade, espaço de pensamento e alteridade: uma análise das cartas de Freud a Fliess - Primo, Joana Sampaio (2015)
The present research set out to investigate the uncanny of an everyday practice: the friendship. Apparently a single phenomenon, soon we noticed that friendship entails many different practices, not only due to its transformations through time, but mainly, because of its different possible inscriptions in a given historical period. We acknowledge friendship as a political practice, in the sense that the in between of friends allows differences to circulate (Arendt, 2010a), building a privileged locus in which three axes come forward: the creation of friendship-practices, of thoughts and of ways of being of otherness and of the self. However, even if friendship resists to its possible time, it is also entangled in the hegemonic discourses. From this double aspect, we took one real friendship relationship as an object. Specifically, we have analyzed the letters from Freud to his friend Fliess, a relationship that took place in the beginning of the development of the psychoanalysis theory. In a first approach, we analyzed these letters as a rich material with many meanings for friendship, relating them to the three axes above mentioned without trying to identify a political friendship per se, but regarding the particularities of the Freud-Fliess relationship. To support friendship as a political practice, that sets a creation locus, we needed to investigate the development of this practice in history. This second moment of our research highlighted some features of friendship that appeared many times in different periods: the intersection among philía and éros, among philía and phrate, the importance of the friend to develop thoughts and the association between a political potency and friendship. We emphasize the alterity and creative aspect as characteristics that articulate, in our research, the analyzes of the Freud-Fliess correspondence and of the friendship's polissemical practices and meanings, as well as important features to the psychoanalysis Moreover, in regard to the political sense of friendship, we affirm that the friend's meetings, the in between of particular and plural tension the distinction between private and public, inscribing friendship as a practice analogous to a plaza, space of action and creation. The singularities of friendship locus of thought, alterity and self , despite being concatenated to the particular relationships, are linked with the common world, as we observe in the friendship between Freud and Fliess and the elaboration of a new theory, the psychoanalysis which forced a different perspective of the world